Mobile Retailing: What Factors are Hindering this Trend? - Patience Anokomah; Bridgett Clinton-Scott (Undergraduate Research Journal for the Human Sciences, 2016)
This paper focuses on the relationship between the retailing industry and mobile shopping by examining consumer shopping preferences for mobile retailing. The major purpose of this research paper is to explore factors that may be hindering mobile shopping from becoming more widely accepted by today’s consumers. This research topic will help retail professionals better understand the influence of mobile retailing and consumer shopping preferences.
Keywords: Mobile; Retailing